Penerapan Metode Elektrokoagulasi Dalam Peningkatan Kualitas Larutan FeCl3.6H2O - Miratsi, Lizia; Kurniawan, Widodo Budi; Indriawati, Anisa (Jurnal Riset Fisika Indonesia, 2024)
Electrocoagulation is a method that is often used to improve the quality of solutions. The electrocoagulation method has the advantages of not using chemical additives, easy and inexpensive operation, and having high efficiency in removing pollutants and contaminants. In this method, the pollutants obtained are easy to separate because of the floating surface of coagulated sediments called flocs. The solution used is FeCl3.6H2O solution as a source of iron content and a replacement medium for water or solutions containing iron. The iron content in water is more dominant than other heavy metals, whereas in excess it can cause health problems. In this study, a standard iron solution was used at 10 ppm variations using the electrocoagulation method using an aluminum plate at a voltage of 25 volts and a time of 60 minutes, and testing for pH, TDS, and UV-Vis was carried out. Obtained after the electrocoagulation process of the Fe standard solution, each concentration experienced an increase in quality, in the form of a significant decrease in Fe concentration (ppm), an increase in the pH value from 3 to 5, and a decrease in the TDS value of 80.69% -85.88%. So, the electrocoagulation method can be applied to improve the quality of a solution.